2015
DOI: 10.1186/s13000-015-0435-5
|View full text |Cite
|
Sign up to set email alerts
|

miR-449a targets Flot2 and inhibits gastric cancer invasion by inhibiting TGF-β-mediated EMT

Abstract: BackgroundFlot2, a highly conserved protein of the SPFH domain containing proteins family, has recently been identified as oncogene to be involved in the tumorigenesis and metastasis of several cancers including gastric cancer. However, the underlying molecular mechanism of Flot2 in gastric cancer (GC) is largely unknown.MethodsqRT-PCR and western blot was performed to detect miR-449a and Flot2 expression in GC cell lines and Normal human gastric epithelial cells. Then, luciferase reporter assay was used to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…Several lines of evidence have implicated that SBD exerts a strong activity of anti-tumour, anti-oxidative stress and anti-inflammation [10][11][12]. Recent studies mainly focused on its anti-tumour effects which have been reported in many kinds of cancers [13][14][15]. Besides, SBD had prominent antioxidant activity and free radical-scavenging property [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have implicated that SBD exerts a strong activity of anti-tumour, anti-oxidative stress and anti-inflammation [10][11][12]. Recent studies mainly focused on its anti-tumour effects which have been reported in many kinds of cancers [13][14][15]. Besides, SBD had prominent antioxidant activity and free radical-scavenging property [19].…”
Section: Discussionmentioning
confidence: 99%
“…Scutellaria barbata D. Don (SBD), also known as Ban-Zhi-Lian, is a perennial herb with multiple pharmacological effects, including anti-inflammation, anti-oxidation and anti-tumour activity [10][11][12]. It has been demonstrated that SBD has a strong inhibitory effect on numerous human cancers, such as lung cancer, hepatocellular carcinoma and skin cancer [13][14][15]. While the antioxidant effect of SBD has been widely accepted, its functional effects on neuronal oxidative injury have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…FLOT2 inhibits cell proliferation, migration and invasion of gastric cancer cells [25]. FLOT2 is up-regulated in gastric cancer and miR-449a reduces cell invasion by inhibiting the expression of Flot2 via TGFb-mediated EMT [26]. FLOT2 is highly expressed in oral squamous cell carcinoma [27], nasopharyngeal carcinoma [28] and non-small cell lung cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Flotillin 1 is a microRNA-124 target in breast tumors [16], and flotillin 2 is a microRNA-485-5p target in non-small-cell lung cancer [62]. In gastric cancer, microRNA-485-5p targets flotillin 1 and microRNA-449a flotillin 2 [63,64]. Gene amplification also might increase flotillin expression level.…”
Section: Flotillin Role In Tumorigenesismentioning
confidence: 99%